Penerapan Metode Need Analysis Pada Karyawan Bank BRI Cabang Ponorogo - Jawwad Sulthon Habiby, S.T., M.T Jawwad (Elsalima (Salam Institute), 2024)
This community service aims to optimize human resources management through the implementation of needs analysis method among employees of Bank BRI Branch Ponorogo. This approach is crucial as it enhances organizational efficiency, effectiveness, and employee welfare. The needs analysis method is employed to identify training and development needs, ensuring that training programs are targeted and impactful. The results indicate an improvement in employees' understanding of their roles and responsibilities, as well as an enhancement in customer service quality. In conclusion, this mentoring has a positive impact on enhancing HR management and organizational performance.